“Compensate the Losers?” Economic Policy and the Origins of U.S. Partisan Realignment - Kuziemko, Ilyana; Longuet-Marx, Nicolas; Naidu, Suresh (Quarterly Journal of Economics, 2026)
We argue that the Democratic Party’s evolution on economic policy helps explain partisan realignment by education. First, we document that educated Americans differentially oppose “predistribution” (e.g., job guarantees, higher minimum wages, protectionism, and stronger unions), while the educational gradient for redistribution (taxes and transfers) is close to zero. These relationships have been largely unchanged since the 1940s. Second, focusing on politicians and donors as key party actors, we show that the Democratic Party has moved away from predistribution since the 1970s. The number of predistribution bills introduced by Democratic House Speakers has declined by half since the 1970s. Unions—the traditional lobbying force for predistribution—see their share of Democratic Party PAC donations decline from 90% to 40% from 1968 to 1980, following 1970s legislation that facilitated corporate PAC donations. From 1980 onward, the Democrats rely increasingly on individual contributions from educated donors relative to the Republicans. We show the increased reliance on corporate PACs and educated donors is driven by the rise of a self-described “New Democrat’’ faction particularly conservative on predistribution and social issues. Finally, we trace the reaction of voters to these changes in the Democratic Party. Less-educated Americans begin to leave the party in the 1970s, after decades of serving as its base. We also show that in the crucial transition period of the 1970s through 1990s, New Democrat candidates outperform other Democrats among more-educated voters in both survey questions and actual Congressional elections. As the New Democrats are more socially conservative than other Democrats, their success with educated voters suggests that social issues alone cannot explain educational realignment.